Highly Efficient TADF OLEDs: How the Emitter–Host Interaction Controls Both the Excited State Species and Electrical Properties of the Devices to Achieve Near 100% Triplet Harvesting and High Efficiency. (8th August 2014) - Jankus, Vygintas; Data, Przemyslaw; Graves, David; McGuinness, Callum; Santos, Jose; Bryce, Martin R.; Dias, Fernando B.; Monkman, Andrew P.
<x xml:space="preserve">Abstract</x> New emitters that can harvest both singlet and triplet excited states to give 100% internal conversion of charge into light, are required to replace Ir based phosphors in organic light emitting diodes (OLEDs). Molecules that have a charge transfer (CT) excited state can potentially achieve this through the mechanism of thermally activated delayed fluorescence (TADF). Here, it is shown that a D–A charge transfer molecule in the solid state, can emit not only via an intramolecular charge transfer (ICT) excited state, but also from exciplex states, formed between the molecule and the host material. OLEDs based on a previously studied D–A–D molecule in a host TAPC achieves >14% external electroluminescence yield and shows nearly 100% efficient triplet harvesting. In these devices, it is unambiguously established that the triplet states are harvested via TADF, but more interestingly, these results are found to be independent of whether the emitter is the ICT state or the D–A–D/host exciplex.